Motivasi Petani Selada Air di Desa Popnam Kecamatan Noemuti Kabupten Timor Tengah Utara - Oktovianus Tabenu; Agustinus Nubatonis; Marsianus Falo; Petrus Suse Kobesi (AGRIMOR, 2023)
Agricultural development in Indonesia is very influential in increasing the selling value of production and business opportunities for farmers originating from several agricultural sub-sectors. One of them is the food crops and horticulture sub-sector. This condition motivates farmers to use land effectively in improving farming in a sustainable manner. The purpose of this research is to describe the motivation of watercress farmers in Popnam Village, TTU Regency. The data collection process uses a survey method of farmers first in order to find out the initial conditions. This study used a mix method approach, namely quantitative data were obtained using Likert scale measurements while qualitative data were obtained through in-depth interviews to explore intrinsic and extrinsic motivation data on farmers. The results of the study explain that intrinsic factor is in the high category with a percentage of 84%. Efforts to meet food needs, build a decent place to live, support each other and work together are very important in the development of farming. The safety and appreciation factors that farmers have strengthens their inner motivation for sustainable farming development. Furthermore, the extrinsic factor is in the high category with a percentage value of 82%. This is seen from the price, market reach, and technology which has a high category. Even though government policies are less effective in terms of attention to farmers, the relationship between farmers is quite close as a family unit in building economic solidarity.